Activation of Purified Prothrombin to Autoprothrombin I or Autoprothrombin II (Platelet Cofactor II or Autoprothrombin II-A) - Mammen, Eberhard F.; Thomas, William R.; Seegers, Walter H. (Thrombosis and Haemostasis, 1961)
Autoprothrombin I, autoprothrombin II, and autoprothrombin II-A have been derived from bovine prothrombin and concentrated.Autoprothrombin I is formed when thrombin is used to activate prothrombin which has been chromatographed on IRC-50 or diethylaminoethyl cellulose. The activation is inhibited by calcium ions, and goes more rapidly as the alkalinity is increased up to pH 9.7. During the activation the liberation of acidic groups predominates over that of the basic groups. In activation mixtures proline, alanine, threonine and valine were found as N-terminal amino acids. The activity was identified with a fraction that contained N-terminal valine, but an alteration can be made with IRC-50 so that the activity is all retained with a change in N-terminal amino acid. The activity is tentatively ascribed to a molecule that has a sedimentation constant of 3.8 in an ultracentrifuge. The autoprothrombin I was found to be soluble in ammonium sulfate solution at 50% of saturation and precipitated when the salt concentration is at 70% of saturation. There was very little loss of activity associated with drying from the frozen state at pH 8.0. Acetone precipitation destroyed the activity, and acidification predisposed to a loss in activity.All prothrombin preparations we have worked with develop autoprothrombin I activity in the presence of platelet factor 3 and calcium ions, but not, if the calcium ions are not there. The solubility of the protein is the same as when obtained by thrombin activation or by separation from serum.Autoprothrombin II is formed when purified thrombin is used to activate non-chromatographed prothrombin. The activation is inhibited with calcium ions, and there is a pH optimum between 7 and 8. During activation nonbuffered solutions become acidic. The activity is identified with a fraction in which the N-terminal amino acid is proline and the C-terminal amino acid is tyrosine. The activity was concentrated in a fraction that was practically homogenous upon ultracentrifuge analysis. The sedimentation constant is near S = 3.7 (tentative). The activity is easily precipitated at 50% of saturation with ammonium sulfate. No activity was lost upon dialysis or drying from the frozen state around pH 7 to 8. The concentrates with autoprothrombin I activity are precipitinogenic against antiprothrombin and anti-bovine serum. The autoprothrombin II of serum is also precipitated at 50% of saturation with ammonium sulfate.Autoprothrombin II-A is an anticoagulant that was found to be closely related to autoprothrombin II in physical chemical characteristics. The anticoagulant had arginine as N-terminal amino acid and tyrosine as C-terminal amino acid. After IRC-50 resin chromatography the autoprothrombin II-A protein was found to be changed and had autoprothrombin II activity, N-terminal proline and C-terminal tyrosine. The autoprothrombin II-A activity was retained during dialysis and during drying from the frozen state. The sedimentation constant found with the ultracentrifuge was 3.8. The activity was also found in concentrates from serum.Autoprothrombin II corrects the recalcified clotting time of PTC deficient plasma. Hemophilia A blood clots rapidly with autoprothrombin II. The recalcified clotting time of hemophilia A plasma is also brought to the normal range with concentrates of autoprothrombin II. In general the prothrombin utilization does not seem to be increased when the procoagulant is added to hemophilic blood or plasma.